The Changing Face of Paediatric Human Growth Hormone Therapy - Martin O. Savage (Endocrines, 2022)
Human growth hormone (hGH) has been used therapeutically to promote growth in children for over 60 years. Pituitary-extracted hGH has demonstrated positive growth promotion since the early 1960s. In 1985, prion-induced contamination of hGH triggered a global epidemic of Creutzfeldt–Jakob disease that was responsible for its discontinuation. Recombinant hGH immediately replaced pituitary hGH and, being available in large amounts, was used and licenced for therapy in GH-deficient children, followed by approval for non-GH deficient disorders such as Turner syndrome, short stature related to birth size small for gestational age, idiopathic short stature, SHOX deficiency, Prader–Willi syndrome and Noonan syndrome. RhGH therapy was refined by the use of growth prediction models; however, unmet needs, such as the variability in response and non-adherence resulted in the development of long-acting rhGH (LArhGH) molecules, which are currently in clinical trials and have shown non-inferiority in comparison with daily rhGH. It is likely that LArhGH will enter clinical practice in 2022 and 2023 and will need to demonstrate safety in terms of immunogenicity, IGF-1 generation, metabolic status and tolerability of potential injection pain and local reactions.